KOHESI SOSIAL MENUJU KELUARGA SAKINAH: STUDI SOSIOLOGIS PADA MASYARAKAT NEGERI HUKURILA, KOTA AMBON - Feky Manuputty; Afdhal Afdhal; Nathalia Debby Makaruku (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The issue of the emergency of family divorces has become an increasingly pressing concern in Indonesia. In facing this challenge, the effort to build harmonious families has become highly important. This article aims to analyze the significant role of traditional and religious values in fostering family harmony. The research employs a qualitative approach with a case study of families in Negeri Hukurila, recognized as a community that upholds cultural values and social solidarity. The research methodology involves qualitative data analysis through in-depth interviews, participatory observations, and document analysis. The research findings reveal that families in Negeri Hukurila play a central role in preserving and transmitting cultural values and social solidarity within the community. Traditional values embedded in family traditions provide a strong foundation for family harmony and stability. Additionally, religion also plays a crucial role in fostering harmony within families. The approaches of pre-marital education and religious instruction have proven to significantly contribute to shaping thought patterns, behaviours, and family member interactions. Pre-marital education equips prospective couples with the necessary skills to navigate the challenges of marriage, while religious education provides a value framework that strengthens familial bonds. The results of this study underscore that the integration of traditional and religious values forms a robust foundation for fostering family harmony. This article provides insights into how the amalgamation of traditional and religious values can address the issue of the emergency of family divorces. It highlights the importance of integrating cultural and religious values to mitigate the challenges of family dissolution.